Perampasan Aset Tindak Pidana Pencucian Uang: Perlindungan Pihak Ketiga Beritikad Baik dalam Perspektif Hukum Indonesia - Harefa, Beniharmoni; Supardi (Jurnal Risalah Hukum, 2025)
Asset forfeiture in money laundering serves as a key tool to disrupt the economic benefits of crime and restore state losses, yet its implementation faces challenges in protecting bona fide third parties. The lack of clear and consistent standards for assessing good faith leads judges to decide case by case, creating legal uncertainty and potential injustice. Normative gaps, including disharmony regarding non-conviction-based forfeiture, exacerbate these ambiguities. This study employs a normative juridical method combining statute, case, and conceptual approaches. The statute approach examines the TPPU Law and the Corruption Eradication Law on asset forfeiture and third-party protection; the case approach analyzes judicial practice, including Decision No. 362/Pid.Sus/2025/PN Jkt.Sel, to assess judges’ interpretation of good faith; the conceptual approach reviews doctrines, principles, and theories on asset forfeiture, property rights, and third-party protection. Findings show that judicial standards remain inconsistent, leaving third-party protection case-specific and legally uncertain. The study highlights the gap between normative frameworks and practice and underscores the urgent need for clearer, proportional standards for proving good faith in the anti-money laundering regime.